A Study of the Feasibility of Using Grey Sedge Residue to Facilitate Zero Waste Production - Kamonwan Chucheep; Nathaporn Suwanpayak; Naree Phanchindawan (Recycling, 2022)
There is approximately 30% of grey sedge (Lepironia articulata) residue remaining from weaving production that could add value to support zero waste management. Therefore, the aim of this research was to study the feasibility of using a residue of grey sedge or Krajood strips from weaving production to form a value-added product. To obtain preliminary data, Krajood strip residue was examined for its biological and physical properties. In addition, the biological and physical properties of Krajood strip residue in combination with loam soil (KSRL) were examined and compared with the properties of loam soil (LS) itself. The results showed that the total microbe and moisture content of the Krajood strip residue was significantly higher than that of the products made from Krajood strips (KS). The stress value of Krajood strips was higher than the stress values of other samples except for that of a bag made of paper. Identification of bacteria and mold by MALDI Biotyper and DNA sequencing compared with BLAST revealed the presence of the types of soil microbes that benefit plants. KSRL was enriched with larger amounts of the primary elements important for plant growth: nitrogen, phosphorus, and potassium, and the three second tier elements. The pH of KS, LS, and KSRL were 6.40 ± 0.14, 5.87 ± 0.04, and 5.26 ± 0.02, respectively. These results could support the use of this beneficial residue for bioresource sustainability.
Keywords: Plant tissue culture and regeneration; Soil Carbon and Nitrogen Dynamics; Composting and Vermicomposting Techniques